Investigation of a Design Review Process for Externally Sourced Components: Challenges in the Process of Developing and Sourcing New Components - Säfdal, Sandra (My University, 2022)
The Defence and Security Company (DSC), has a variety of extremely complex products with high requirements. Even though the DSC has a production, the complexity of the products demands that some components are bought from suppliers. Some components can be bought from suppliers "off the shelf" without further modifications but many components are developed by the company or needs modifications to satisfy the need. To make sure that the company communicates the right needs to an external supplier, a product specification is created for each component developed by the DSC or in need of modification. The product specification should include drawings and requirement specifications detailed enough for the supplier to manufacture the wanted component. Due to the time frame for the developing project not always following the time frame for the delivery of components, the product specification is not always completed when the external supplier is contacted. This does not just make it hard for the supplier to create a good enough product, but the very choice of which supplier to choose is affected. Also, the documented process is not always followed and risk analyses are not always conducted. This leads to problems as the project goes and in the end, the manufactured product might not fulfill the requirements set by the company or the requirements are not extensive enough. The theoretical contribution is based on lean management, root cause analysis with the 5-whys, project models, product specification, cultural influences within an organization and Failure Mode and Effects Analysis (FMEA). The study was executed by conducting exploratory, semi-structured interviews with stakeholders of the process and by investigating documentations and regulations. The proposed solution to this is to conduct a risk analysis early in the development process to identify the risks and the complexity of the component. The risk analysis is then used to rank the component as high risk or low risk. Depending on the ranking of the component, it can be decided on how extensive the product specification needs to be and where there is a need for control points in the process.
Keywords: components, complexity, requirements, specification, supplier, process, risk, ranking, control, study